Hubungan Tingkat Pengetahuan Terhadap Perilaku Penyimpanan Dan Pembuangan Obat Pada Masyarakat Di Sumberagung Kecamatan Ambarawa - Hasanah, Uswatun; Pratiwi, Mida; Ayu, Fadillah (Jurnal Ilmiah Wahana Pendidikan, 2025)
Medication that has expired or is no longer needed can pollute the environment, raise the possibility of toxicity, and be purposefully misused. According to preliminary findings, drug providers' failure to offer adequate information on drug storage and disposal practices contributes to people's ignorance or perplexity about how to appropriately dispose of drug waste. This research objective was to determine the level of knowledge and behavior of the community in Sumberagung Village, Ambarawa District regarding the storage and disposal of medicines and the correlation between the level of knowledge and the storage and disposal of medicines in the community in Sumberagung Village of Ambarawa Sub-District. This type of research is quantitative descriptive with a cross sectional method using 26 statement items for knowledge and 10 question items for behavior. The sample in this study was 98 people from Sumberagung Village, Ambarawa District. The research results showed that the level of public knowledge about proper storage and disposal of medicines was 5 (5.10%) respondents, 5 (5.10%) respondents in the sufficient category and 88 (89.80%) respondents in the inadequate category. The level of community behavior regarding proper storage and disposal of medicines was 9 (9.2%) respondents, the adequate category was 45 (45.9%) respondents and the inadequate category was 44 (44.9%) respondents. Based on the SPSS test results using the correlation test, the results were sig (2-tailed) < sig 0.05 (0.03 < 0.05), it can be concluded that there is a correlation between the level of knowledge and drug storage and disposal behavior in the community in Sumberagung, Ambarawa Regency